2013
DOI: 10.3164/jcbn.13-48
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the hepatic stearoyl-CoA desaturase 1 gene in offspring after isocaloric administration of high fat sucrose diet during gestation

Abstract: Adverse early nutrition leads to metabolic aberrations in adulthood. Molecular and cellular mechanisms responsible are emerging; specific nutritional causes remain unclarified. We investigated gestational dietary intake and its influences on metabolism in offspring. Three groups of pregnant Sprague-Dawley rats were fed either AIN93G standard diet as control, isocaloric high fat sucrose diet or calorie restriction diet (50% of control) until delivery. All dams were fed control diet ad libitum during lactation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In support of this, SCD‐1 expression has previously been shown to be increased in the liver of 3‐week‐old offspring of dams fed a high‐fat and high‐sucrose diet during pregnancy (Wanjihia et al . ) and in 6‐month‐old offspring exposed to a high‐fat diet during both the fetal and suckling periods (Seet et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, SCD‐1 expression has previously been shown to be increased in the liver of 3‐week‐old offspring of dams fed a high‐fat and high‐sucrose diet during pregnancy (Wanjihia et al . ) and in 6‐month‐old offspring exposed to a high‐fat diet during both the fetal and suckling periods (Seet et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the increased Scd1 expression we observed in HF offspring is likely a compensatory response reflective of a state of metabolic stress in the adipose tissue. A number of other programming studies have demonstrated increased expression and/or activity of SCD1 in offspring exposed to adverse maternal environments, including a HF and sucrose diet 39 , HF diet 40 and maternal IR 41 . However, these studies only investigated SCD1 in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, high-fat, high-sucrose (HFS) diets, simulating a Western diet, when fed to rodent models result in increased body weight and abdominal fat deposition, hyperinsulinaemia, and hyperglycaemia (11) . Moreover, HFS exposure in utero has been shown to alter glucose, insulin and lipid homoeostasis (12)(13)(14) and induces adipose accumulation and fatty liver in adult rodent offspring (13,15) . The precise mechanism by which gestational HFS exposure alters glucose and insulin homoeostasis and the expression of genes and proteins associated with insulin signalling and lipid metabolism remains largely unknown.…”
mentioning
confidence: 99%